Nigerian banking structure and performance : the banking system's contribution to economic development - Agu, C. C.; Gardener, Edward P. M. (Onitsha, Nigeria : African-FEP Publishers, 1988)
The book tries to show that within the context of Nigeria's development effort, financial development with respect to the banking system has aided investment and economic development to a greater extent than is generally recognized.
Includes bibliographical references (p. 191-217).
osc 27/07/2018, ijb 14/03/2019
Loans
Keywords: Banks and banking; Nigeria